REPRESENTASI BERLALU LINTAS PENGGUNA MOTOR GEDE PADA VIDEO BLOG RG700 - Ramadhan, Febiano; Purnawan, Ni Luh Ramaswati; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2020)
ABSTRACT Various kinds of content are available on Youtube to be watched, such as a vlog content about bikers that are used as a means of information. Some riders of bikers in Vlog RG700 showed a habit which made another riders felt uncomfortable. A sign that represented discomfort by riders in the RG700 vlog was analyzed using John Fiske's Semiotic Theory. The results showed that another riders in the RG700 vlog gave uncomfortable feelings such as riding at high speed, using excessive accessories, joking on the road, asking for priority, and harming other road users. What appeared in the vlog will be better if it is filtered before being followed and do some things that do not violate existing regulations. Keywords:Hedonism, Representation, Semiotics, Youtube.